Follow‐up and clinical significance of unsatisfactory liquid‐based Papanicolaou tests. Issue 1 (23rd October 2014) - Owens, Christopher L.; Buist, Diana S.M.; Peterson, Daniel; Kamineni, Aruna; Weinmann, Sheila; Ross, Tyler; Williams, Andrew E.; Stark, Azadeh; Adams, Kenneth F.; Doubeni, Chyke A.; Field, Terry S.
Abstract : BACKGROUND: To the authors' knowledge, few studies to date have examined adherence to recommended guidelines for follow‐up and outcomes after an unsatisfactory Papanicolaou (Pap) test (UPT) with liquid‐based technologies. METHODS: Within 4 US health plans, the median time to follow‐up and the percentage of patients with follow‐up testing by 120 days was calculated after a UPT. Multivariable analyses evaluated the association between clinical factors and follow‐up testing. The authors compared the risk of a diagnosis of cervical intraepithelial neoplasia of type 2 or worse (CIN2+) after a UPT with the risk after a satisfactory Pap test while controlling for study site, test year, and other covariates. RESULTS: A total of 634, 644 Pap tests performed between 2004 and 2010 were included in the current study. Of 1442 UPTs, 53.4% had follow‐up testing within 120 days; follow‐up differed across the health plans ( P <.001) and was found to be higher among patients aged <50 years (57.2% vs 48.8%; P = .01) and those with positive human papillomavirus (HPV) results (84.6% vs 53.9; P <.01). The risk of CIN2+ was similar for patients with both unsatisfactory and satisfactory Pap tests. However, after a UPT, the variables of age <50 years, having no previous history of Pap testing, having a history of a previous abnormal Pap test, and positive HPV status were all found to be risk factors for CIN2+; a positive HPV test was found to be the strongest risk factor for developing CIN2+. A negative HPV test result was protective for a CIN2+ diagnosis. CONCLUSIONS: Various clinical factors associated with the risk of CIN2+ appear to influence the receipt of follow‐up after a UPT. HPV test results in patients with UPTs might be used in follow‐up strategies; specifically, a negative test result might reduce the urgency for repeat Pap testing. Cancer (Cancer Cytopathol) 2015;123:59–65 . © 2014 American Cancer Society . Abstract : Various clinical factors influence the receipt of guideline‐recommended follow‐up studies after an unsatisfactory Papanicolaou test. The results of high‐risk human papillomavirus testing demonstrate promise for stratifying the risk after an unsatisfactory Papanicolaou test.